2009
DOI: 10.1016/j.yexmp.2008.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Response gene to complement 32 is required for C5b-9 induced cell cycle activation in endothelial cells

Abstract: Proliferation of vascular endothelial cells (EC) and smooth muscle cells (SMC) is a critical event in angiogenesis and atherosclerosis. We previously showed that the C5b-9 assembly during complement activation induces cell cycle in human aortic EC (AEC) and SMC. C5b-9 can induce the expression of Response Gene to Complement (RGC)-32 and over expression of this gene leads to cell cycle activation. Therefore, the present study was carried out to test the requirement of endogenous RGC-32 for the cell cycle activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
77
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 35 publications
4
77
0
Order By: Relevance
“…Recently, some studies have reported that Akt activation participated in C5a-induced RGC32 expression in breast cancer cells [30] and hyperglycemia-or hyperinsulinemia-induced RGC32 expression in endothelial cells [31]. Meanwhile, other studies have shown that RGC32 silencing inhibited C5b-9-mediated Akt phosphorylation in human aortic vascular endothelial cells [32]. The above studies implied that the relationship between AKT and RGC32 is changeable at different conditions and in different cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies have reported that Akt activation participated in C5a-induced RGC32 expression in breast cancer cells [30] and hyperglycemia-or hyperinsulinemia-induced RGC32 expression in endothelial cells [31]. Meanwhile, other studies have shown that RGC32 silencing inhibited C5b-9-mediated Akt phosphorylation in human aortic vascular endothelial cells [32]. The above studies implied that the relationship between AKT and RGC32 is changeable at different conditions and in different cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in contrast with previously reported data on the RGC-32-mediated activation of AKT in endothelial cells. 36 In addition, An et al 16 reported that RGC-32 had no significant effect on the phosphorylation of Akt in human umbilical vein endothelial cells. 16 The disparities among these reports might reflect differences in RGC-32 functions in different cell types.…”
Section: Cd14mentioning
confidence: 99%
“…Upon complement activation, its individual components C5b, C6, C7, C8, and C9 combine to form a lytic pore on the surface of target cell membranes in response to activated complement, capable of inducing cell lysis and inflammatory processes, as well as activating various cell signalling pathways. 6,7 The formation of MAC is regulated by the membrane bound complement regulatory protein CD59, which controls activation of complement by inhibiting the incorporation of C9 into the forming complex, and thereby preventing assembly of a functional pore. 8,9 CD59 is strongly expressed in the normal human retina and in cultured retinal pigment epithelial (RPE) cells.…”
Section: Introductionmentioning
confidence: 99%